Critical review of superplastic magnesium alloys with emphasis on tensile elongation behavior and deformation mechanisms - H.T. Jeong; W.J. Kim (Journal of Magnesium and Alloys, 2022)
The tensile elongation behavior and deformation mechanisms of superplastic Mg alloys and Mg composites were examined by extensively reviewing the literature published from the time of the first report on the superplasticity of Mg alloys to the present day. Studies on the superplasticity of Mg alloys have been conducted mainly on Mg-Al-Zn (AZ) series alloys, Mg-Zn-Zr (ZK), Mg-Li and Mg-RE (rare earth) alloys, and in recent years, Mg-RE alloys have attracted the greatest attention. The effect of grain size and the type and amount of secondary phase particles on the superplasticity of Mg alloys was systematically examined and reviewed. The alloys processed by severe plastic deformation (SPD) and powder-metallurgy methods have smaller grain sizes and exhibit superior superplasticity compared to conventionally processed (by extrusion and rolling) Mg alloys. For the AZ alloys, as the volume fraction of the Mg17Al12 phase increases, smaller grains are obtained, and the low-temperature superplasticity (LTS) and high-strain-rate superplasticity (HSRS) characteristics become enhanced. The ZK60 alloy with finely dispersed MgZn2 particles exhibits excellent LTS, while the Mg-RE alloys with a high fraction of thermally stable particles exhibit excellent HSRS. Mg-Li alloys can exhibit LTS even at room temperature due to the presence of a high-volume fraction of the body centered cubic (BCC) phase where atomic diffusivity is high. Grain boundary diffusion- and lattice diffusion-controlled grain boundary sliding are found to operate as the dominant deformation mechanisms below ~ 473 K and above ~ 673 K, respectively, at small grain sizes. Deformation mechanism maps were constructed based on the analysis of the deformation behavior of superplastic Mg alloys, and from the maps, the critical conditions for achieving LTS, HSRS and simultaneous achievement of LTS and HRSR were calculated and proposed, and their importance was discussed.